VARIATION OF MANIHOT AMYLUM AS A DISINTEGRANT IN TABLET FORMULATION RESULTS WITH THE ACTIVE INGREDIENTS PARACETAMOL, IBUPROFEN AND CAFFEINE - Juvita Herdianty; Nola Nonita Nengsieh (Strada Journal of Pharmacy, 2020)
In general, oral medications must first dissolve in digestive fluids before they can be absorbed through the intestinal wall. Therefore, increasing the dissolution rate is a rate determining step that can increase drug absorption, especially for substances that are difficult to dissolve (Giang, T.P. 1987). One drug that is difficult to dissolve is ibuprofen. Ibuprofen is an analgesic, antipyretic, non-steroidal anti-inflammatory drug with water solubility of 0.049 mg/ml and is almost insoluble (Bhattamishra, S.D and Padhy, R.K. 2009). In addition to the active ingredients, tablets can also contain excipients such as diluents, binders, disintegrants, lubricants (lubricants, non-stick agents, glidants) and in some cases can contain flavoring or coloring agents. (Shamsuni, 2007). Ibuprofen in Ibuprofen in the Class II Drug biopharmaceutical classification system has poor solubility and is very permeable (Dressman and Butler, 2001). Ibuprofen is too uniform and has poor flow characteristics (Resenack, Muller, 2002). This study aims to formulate and evaluate the physical quality results of manihot amylum with desintegran of 3%, 5% and 10%. Experimental research method to determine variations in the concentration of manihot amylum Observation of the results of evaluating the physical quality of the preparation includes organoleptic tests, water content, flow time, repose angle, pH, disintegration time test and tablet hardness testing. The results of this research indicate that there is an influence of differences in the concentration of manihot amylum has a There is a water content test for all formulations that meet the requirements, namely <5%. In the test, the disintegration time of the formulation met the requirements, namely less than 15 minutes. The pH test of all formulations meets the requirements. In the flow time test all formulations met the requirements. In the angle of repose test the preparation meets the requirements. However, when the tablet hardness test does not meet the requirements, it can occur due to the influence of the binder used in the formulation